(untitled) (BIBECHANA, 2016)
A semi-empirical approach has been considered to study the temperature dependence of entropy of mixing, (ΔsM), for various alkai-alkali alloys using hard-sphere model. The most important physical parameters occurring here is the hard-sphere diameter (σ) and the packing fraction (η). For pure liquid metals, this is usually determined empirically from the observed entropy as a function of temperature which in turn are utilised to compute ΔSM for Na-K, K-Rb, Na-Rb, NaCs, Rb-Cs and K-Cs alloys as a function of concentration at five different temperature ranging from 400°K-800°K. The study reveals that entropy of mixing for Na-K, Na-Rb and K-Rb systems decreases with increasing temperature. But the result for Cs-based alloys exhibit a mixed behaviour. BIBECHANA 14 (2017) 16-29